The Use of Digital Fabrication as a Sketching Tool in The Architectural Design Process - Agirbas, Asli (Ecaade-Education & Research Computer Aided Architectural Design Europe, 2015)
Computer-aided manufacturing (CAM) technologies including computer numerically controlled (CNC) milling, laser cutting and 3D printing are becoming cheaper and globally more accessible. Accordingly, many design professionals, academics and students have been able to experience the benefits and challenges of using digital fabrication in their designs. The use of digital fabrication in the education of architecture students has become normal in many schools of architecture, and there is a growing demand for computer-aided manufacturing (CAM) logic and fabrication knowledge in student learning. Clearly, architecture students are acquiring material base-thinking, time management, production methods and various software skills through this digital fabrication. However, it appears to be the case that architecture students use digital fabrication mainly in the final stage of their design or in their finishing work. In this study, computer-aided manufacturing (CAM) technologies have been used as a sketch tool rather than simply for fabricating a final product in the architectural design process and the advantages of this educational practice are demonstrated.
Keywords: Digital Fabrication; Teaching Methodology; Sketching